Age differences in online social networking - Arjan, Rajiv; Pfeil, Ulrike; Zaphiris, Panayiotis (My University, 2008)
This study presents an analysis of age-related differences of user behavior in the social network site MySpace.com. We focus on two age groups: older people (60+ years of age) and teenagers (between 13 and 19 years of age). We used locally developed web crawlers to collect large sets of data from MySpace’s user profile pages. We used different analytic techniques to quantify any differences that exist in the networks of MySpace friends of older people and teenagers. Content analysis was applied to investigate age-related differences concerning the way users represent themselves on their profile pages. Our findings show that teenagers tend to have much larger networks of friends compared to older users. Also, we found that the majority of teenage users’ MySpace friends are in their own age range (age +/- 2 years), whilst older people’s friends tend to have a more diverse age distribution.
Keywords: Ageing; Computer-mediated communication; Social networking sites